Social protection policies and fertility: How can social protection measures address the low fertility rate in Germany? - Nana Germanie Musim (Hochschule Bonn-Rhein-Sieg, Fachbereich Sozialpolitik und Soziale Sicherung, 2024)
There are about 30 low-fertility countries globally. Germany has been a low-fertility country for more than 50 years which is longer than any other country since the lowfertility trend in other countries only began ten or twenty years ago. Low-fertility rates have mainly negative consequences for various policy areas such as pension, health care, economy, labour market, culture, elections, and international relations (Bujard, 2015a, pp. 53f.). Understanding the potential impact of social protection policies on fertility rates is crucial for policymakers who seek to address declining fertility rates by applying evidence-based strategies. By investigating the relationship between these two variables, valuable insights can be gained, informing the design and implementation of effective policies aimed at promoting higher fertility rates and ensuring sustainable demographic outcomes. This research's objective is to identify how social protection measures address the low fertility rates in Germany. To do that, the outcomes of recent social protection measures in Germany related to the fertility rate will be assessed by generating empirical evidence. Consequently, conclusions will be drawn, and suggestions will be offered on how to improve fertility rates.
urn:nbn:de:hbz:1044-opus-84989
Keywords: 360; Fertility rate; Demography; Socio-political challenges; Financial sustainability; National social protection systems